Effects of evidence-based nursing under a quantitative assessment strategy on cancer-related fatigue, self-management ability, and quality of life in lung cancer patients undergoing chemotherapy - Zhang, Liwei; Fang, Haixian; Zhang, Yongqian; Su, Xin; Zhang, Juan; He, Li; Bo, Changwen; Yan, Yusha; Liu, Jing; Wang, Feifei (Frontiers in Oncology, 2025)
ObjectiveTo investigate the effects of evidence-based nursing under a quantitative assessment strategy (EB-NQAS) on cancer-related fatigue (CRF), self-management ability, quality of life (QoL), and adverse events in lung cancer patients undergoing chemotherapy.MethodsA single-center, prospective, randomized controlled trial (RCT) was conducted, enrolling 150 lung cancer patients undergoing chemotherapy between January 2024 and January 2025. Participants were randomized into the intervention group (n=75) and control group (n=75) using a random number table. The intervention group received EB-NQAS, which featured personalized care plans based on symptom quantification via the Edmonton Symptom Assessment Scale (ESAS), while the control group received routine nursing care. Outcomes were assessed at baseline and 3 months. CRF was assessed using the Piper Fatigue Scale (PFS), self-management ability via the Adult Health Self-Management Scale (AHSMSRS), and QoL via the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC-QLQ-C30). Adverse events were recorded. Data were analyzed using linear mixed-effects models and chi-square tests.ResultsAnalyses were conducted on all 150 randomized participants per the intention-to-treat principle. After 3 months, the EB-NQAS group showed a significantly greater reduction in the total PFS score compared to the control group (22.88 ± 1.72 vs. 25.36 ± 1.63; group × time interaction, P<0.001). The intervention group also demonstrated significantly greater improvements in total AHSMSRS scores (146.00 ± 9.77 vs. 128.45 ± 12.45) and global health status/QoL scores (77.66 ± 9.74 vs. 68.91 ± 9.51) than the control group (all group × time interactions, P<0.001). The incidence of gastrointestinal reactions in the intervention group (5.33%) was lower than that in the control group (18.67%, P = 0.012). No significant differences were observed in other adverse events (P>0.05).ConclusionEvidence-based nursing under a quantitative assessment strategy effectively reduces CRF, improves self-management ability and QoL, and decreases gastrointestinal reactions in lung cancer patients undergoing chemotherapy, demonstrating strong potential for clinical application.